Perception of 'Comprehensiveness of Care': a qualitative study amongst dentists in the Brazilian Health System - Grazielle Christine Maciel MATTOS; Jennifer Elizabeth GALLAGHER; Saul Martins PAIVA; Mauro Henrique Nogueira Guimarães ABREU (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Comprehensiveness relates both to the scope of services offered and to a holistic clinical approach. The aim of this study was to identify the perception of Brazilian dentists regarding key concepts of comprehensiveness and its importance in primary health care oral health services performed in the public sector. Focus groups were conducted to explore three main concepts, 'patient welcoming', 'bonding' and 'quality of care', as well as their aspects. In total, there were four focus groups comprising seven general dentists, all of whom had at least two years of experience in primary care, from municipalities of varying sizes. Discussions of approximately 60 minutes were conducted, audio-recorded and transcribed. The data were analysed by qualitative thematic analysis, in line with the framework approach. The general dentists reported that they are aware that in the Brazilian Health System, the onset of patient care by primary health care services must happen through 'patient welcoming.' Nevertheless, they suggested that this action is often performed poorly due to the large volume of patients. Although they knew the importance of 'bonding', they realised that there is a lack of education preparing professionals to address interpersonal and social issues. They were aware that 'quality of care' is related to multiple factors. Comprehensiveness, as an approach in dental public health practices, needs to be enhanced, and there is evidence that primary care dentists are aware of the need for such an approach.